EHD Proteins Associate with Syndapin I and II and Such Interactions Play a Crucial Role in Endosomal Recycling - Braun, Anne (The American Society for Cell Biology, 2005)
EHD proteins were shown to function in the exit of receptors and other membrane proteins from the endosomal recycling compartment. Here, we identify syndapins, accessory proteins in vesicle formation at the plasma membrane, as differential binding partners for EHD proteins. These complexes are formed by direct eps15-homology (EH) domain/asparagine proline phenylalanine (NPF) motif interactions. Heterologous and endogenous coimmunoprecipitations as well as reconstitutions of syndapin/EHD protein complexes at intracellular membranes of living cells demonstrate the in vivo relevance of the interaction. The combination of mutational analysis and coimmunoprecipitations performed under different nucleotide conditions strongly suggest that nucleotide binding by EHD proteins modulates the association with syndapins. Colocalization studies and subcellular fractionation experiments support a role for syndapin/EHD protein complexes in membrane trafficking. Specific interferences with syndapin–EHD protein interactions by either overexpression of the isolated EHD-binding interface of syndapin II or of the EHD1 EH domain inhibited the recycling of transferrin to the plasma membrane, suggesting that EH domain/NPF interactions are critical for EHD protein function in recycling. Consistently, both inhibitions were rescued by co-overexpression of the attacked protein component. Our data thus reveal that, in addition to a crucial role in endocytic internalization, syndapin protein complexes play an important role in endocytic receptor recycling.